2021
DOI: 10.31128/ajgp-07-20-5543
|View full text |Cite
|
Sign up to set email alerts
|

Update on the management of infant and toddler developmental dysplasia of the hip

Abstract: This article is the third in a commissioned series on paediatric orthopaedics.Update on the management of infant and toddler developmental dysplasia of the hip Clinical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…If there is an anatomical abnormality in the proximal femoral, femoral osteotomy should be considered to achieve the reduction. Additionally, in late-presenting children, due to the unpredictable remodeling potential of the acetabulums, acetabular osteotomy can be done [5]. A systematic review conducted in Saudi Arabia shows a prevalence of DDH of about 10.46 per 1000 in the Saudi population, with the majority of cases presenting after 12 months [6].…”
Section: Barlow Maneuvermentioning
confidence: 99%
See 1 more Smart Citation
“…If there is an anatomical abnormality in the proximal femoral, femoral osteotomy should be considered to achieve the reduction. Additionally, in late-presenting children, due to the unpredictable remodeling potential of the acetabulums, acetabular osteotomy can be done [5]. A systematic review conducted in Saudi Arabia shows a prevalence of DDH of about 10.46 per 1000 in the Saudi population, with the majority of cases presenting after 12 months [6].…”
Section: Barlow Maneuvermentioning
confidence: 99%
“…Based on the analyzed data, participants were asked about the influencing factors of DDH, and in response to the first question regarding the presence of a child with DDH, the majority (1,206, 97.9% participants) answered no, while 26 (2.1%) reported that their children had been affected. When asked about the timing of the diagnosis, the majority were diagnosed at birth up to six months, accounting for 1.4% ( 17), followed by six months to a year, with a rate of 0.4% (5). Additionally, an equal percentage of participants, 0.2% (2), reported being diagnosed within one or two years.…”
Section: Baseline Sociodemographic Characteristics and Personal Risk ...mentioning
confidence: 99%
“…Early detection is critical as late diagnosed hip dysplasia often results in long term complications and disability. The likelihood of surgical interventions such as closed or open reduction, and femoral or pelvic osteotomies are much higher as are risks for avascular necrosis of the femoral head with early osteoarthritis and associated need for arthroplasty (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in the United Kingdom, screening programs rely more heavily on targeting high-risk populations [ 12 ]. In contrast, Australia does not recommend routine screening using physical examination, instead focusing on high-risk populations, such as infants with a family history of DDH or those born in the breech position [ 13 , 14 ]. Similarly, in Canada, universal screening is not recommended and screening is targeted towards high-risk populations using a combination of physical examination and imaging modalities [ 15 ].…”
Section: Introductionmentioning
confidence: 99%